2021
DOI: 10.3389/fpsyt.2021.739356
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Week Yoga vs. Aerobic Cycling Initiation in Sedentary Healthy Subjects: A Behavioral and Multiparametric Interventional PET/MR Study

Abstract: Interventional yoga studies with an active control group remain scarce and are important to clarify the underlying neurobiology. We conducted an interventional study in healthy controls using simultaneous positron emission tomography/magnetic resonance (PET/MR) imaging and psychometric scales. Thirty healthy, female volunteers (28.4 ± 8.4 years) participated and were randomly assigned to a 12-week yoga or indoor cycling intervention. Before and after the intervention, [18F]FDG and [11C]UCB-J PET was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Our findings on the dose-response are consistent with the previous meta-analysis reporting that improvements in sleep quality were greater when the intervention’s frequency, duration, and total duration were achieved [ 10 ]. Several studies have shown that only MBM intervention longer than three months leads to significant improvements in metabolic profiles [ 101 , 102 ], proinflammatory cytokine [ 103 ], and mental health [ 104 , 105 , 106 ]. Furthermore, the inverted U-shaped hypothesis proposes that moderate-intensity exercise has the most significant cognitive benefits [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on the dose-response are consistent with the previous meta-analysis reporting that improvements in sleep quality were greater when the intervention’s frequency, duration, and total duration were achieved [ 10 ]. Several studies have shown that only MBM intervention longer than three months leads to significant improvements in metabolic profiles [ 101 , 102 ], proinflammatory cytokine [ 103 ], and mental health [ 104 , 105 , 106 ]. Furthermore, the inverted U-shaped hypothesis proposes that moderate-intensity exercise has the most significant cognitive benefits [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…The brain processes involved in these activities may be different from those involved in a simpler form of physical exercise. It has indeed been suggested that yoga and dance could have different effects on the brain from traditional forms of physical exercise (Rehfeld et al, 2018 ; van Aalst et al, 2021 ; Kaur et al, 2022 ). Analysis was not restricted to studies including a control for the interventions (i.e., a “placebo” or “sham” intervention), and no additional restriction was applied to the control condition when included (i.e., for two studies evaluating the effect of PE, control condition could either be resistance or balance training).…”
Section: Methodsmentioning
confidence: 99%